(untitled) - Ephraim Katz (New York, 1994)
The book covers more than 7000 entries on directors, producers, stars, screenwriters and cinematographers. It provides the motion picture studios and film centers; presents styles, genres and schools of filmaking, film-related organizations and events, nad industry jargon and technical terms
Keywords: motion pictures - encyclopedias